Dierentuin Den Haag: mobilisatie-vergadering voor het Plan. Van links naar rechts: Stokvis, Albarda, ?, de la Bella, ?
Dierentuin Den Haag: mobilisatie-vergadering voor het Plan. Van links naar rechts: Stokvis, Albarda, ?, de la Bella, ?